Parental Engagement as a Predictor of Academic Performance among Secondary School Learners in Sheema District, Uganda - Mugumya, Duncans; Karooro, Emmanuel; Mwesigye, Adrian Rwekaza (American Journal of Psychology, 2023)
Purpose: Globally, parents' engagement in their children's education has been found to result in improved academic success. This study investigated the prediction effect of parental engagement on students’ academic performance in government grant-aided secondary schools in Sheema District, South Western Uganda. Methodology: The study used quantitative approach employing cross-sectional survey design. Participants included senior four students, parents of senior four students, and teachers teaching in senior four class. The participants were selected using simple random sampling technique. Data on parental engagement and learners’ academic performance were collected using a 5-point Likert scale questionnaire. Findings: Study results indicated a statistically significant effect of parental engagement in provision of basic needs (t = 5.242, p< .05), academic communication (t = 6.116, p< .05), decision making (t = 5.834, p< .05), infrastructural development and maintenance at school (t = 5.525, p< .05), provision of conducive learning environment (t = 6.819, p< .05), provision of adequate learning resources (t = 6.167, p< .05) on learners’ academic performance. However, the combined effects of parental engagement aspects did not significantly predict learners’ academic performance. The results imply that parental engagement in learners’ educational pursuit should be encouraged so as to enhance learners’ academic performance. Recommendation: It is therefore recommended that school programmes that can compel parents to participate in educational activities should be deliberately instituted so as to enhance academic performance among learners.
Keywords: Parental engagement; Academic performance; Predictor; Secondary school